PERBANDINGAN PENDAPATAN USAHATANI JAGUNG SEBELUM DAN SESUDAH MENERIMA BANTUAN SARANA PRODUKSI PERTANIAN PADA KELOMPOK TANI GOTONG ROYONG DI DESA LOLAH SATU KECAMATAN TOMBARIRI TIMUR KA-BUPATEN MINAHASA (Comparison of Income of Corn Farming Before and After Ceceiving Assistance of Agricultural Production Facilities in the "Gotong Royong" Farmer Group in Lolah Satu Village, East Tombariri District, Minahasa Regency) - Wihelmina Novita Aroran; Lyndon R. J. Pangemanan; Benu Olfie L. Suzana (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aimed to compare the income of corn farming before and after receiving assistance of agricultural production facilities in the "Gotong Royong" Farmer Group in Lolah Satu Village, East Tombariri District. This research was conducted from November 2019 until March 2020. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with corn farmers totaling of 10 respondents using questionnaires, while secondary data were obtained from literature and previous research. The sampling method used in this study was the saturated sampling (census) method in which all populations in the study were selected. The results showed that there were significant income differences before and after receiving agricultural production facilities assistance from the government. This assistance could increase the amount of corn crop production and reduce production costs so that it could increase the income of corn farmers in the "Gotong Royong" Farmers Group.Keywords: Comparison of Income, Corn Farming, Agricultural Production Facility Assistance